CD4 Cell Count Threshold for Cryptococcal Antigen Screening of HIV-Infected Individuals: A Systematic Review and Meta-analysis. (4th March 2018) - Ford, Nathan; Shubber, Zara; Jarvis, Joseph N; Chiller, Tom; Greene, Greg; Migone, Chantal; Vitoria, Marco; Doherty, Meg; Meintjes, Graeme
Abstract: Background: Current guidelines recommend screening all people living with human immunodeficiency virus (PLHIV) who have a CD4 count ≤100 cells/µL for cryptococcal antigen (CrAg) to identify those patients who could benefit from preemptive fluconazole treatment prior to the onset of meningitis. We conducted a systematic review to assess the prevalence of CrAg positivity at different CD4 cell counts. Methods: We searched 4 databases and abstracts from 3 conferences up to 1 September 2017 for studies reporting prevalence of CrAg positivity according to CD4 cell count strata. Prevalence estimates were pooled using random effects models. Results: Sixty studies met our inclusion criteria. The pooled prevalence of cryptococcal antigenemia was 6.5% (95% confidence interval [CI], 5.7%–7.3%; 54 studies) among patients with CD4 count ≤100 cells/µL and 2.0% (95% CI, 1.2%–2.7%; 21 studies) among patients with CD4 count 101–200 cells/µL. Twenty-one studies provided sufficient information to compare CrAg prevalence per strata; overall, 18.6% (95% CI, 15.4%–22.2%) of the CrAg-positive cases identified at ≤200 cells/µL (n = 11823) were identified among individuals with a CD4 count 101–200 cells/µL. CrAg prevalence was higher among inpatients (9.8% [95% CI, 4.0%–15.5%]) compared with outpatients (6.3% [95% CI, 5.3%–7.4%]). Conclusions: The findings of this review support current recommendations to screen all PLHIV who have a CD4 count ≤100 cells/µL for CrAg and suggest that screening may be considered at CD4 cell count ≤200 cells/µL.